2003
DOI: 10.1177/096739110301100206
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the Properties of Polyethylene with Chlorinated Polyethylene (CPE)

Abstract: Blends of high density polyethylene (HDPE) and chlorinated polyethylene (CPE) have been tested across the whole concentration range. Polyethylene is used to modify the properties of CPE in the elastomer industry, but modification of the properties of polyethylene with CPE is still not usual. Conventional mechanical tests and dynamic mechanical tests were carried out. The blends were found to be multiphase systems of excellent technological compatibility. Between 10 and 15% by weight CPE increased the modulus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
(1 reference statement)
0
3
0
Order By: Relevance
“…In the research published so far, it is necessary to mention the references that have shown the high efficiency of combining waste polyethylene with a copolymer and an elastomer in manufacturing a material that can be effectively used in industry [23,24]. Marossy [25] and Záraga [26] analysed the effect of chlorinated polyethylene in PVC/PE blends and found that polyethylene improves its rigidity if the concentration of chlorinated polyethylene is not too high. Kollar and co-authors [27] demonstrated that a blend of polyvinyl chloride with polyethylene can be obtained by melt blending using high-and low-density polyethylene, without the use of a stabilizer.…”
Section: Comparative Analysis Of Mechanical Properties Of Recycled Pl...mentioning
confidence: 99%
“…In the research published so far, it is necessary to mention the references that have shown the high efficiency of combining waste polyethylene with a copolymer and an elastomer in manufacturing a material that can be effectively used in industry [23,24]. Marossy [25] and Záraga [26] analysed the effect of chlorinated polyethylene in PVC/PE blends and found that polyethylene improves its rigidity if the concentration of chlorinated polyethylene is not too high. Kollar and co-authors [27] demonstrated that a blend of polyvinyl chloride with polyethylene can be obtained by melt blending using high-and low-density polyethylene, without the use of a stabilizer.…”
Section: Comparative Analysis Of Mechanical Properties Of Recycled Pl...mentioning
confidence: 99%
“…Also Marossy [29] proved that the low polyethylene content in the PVC mixture improves the stiffness. According to Arnold [30], impurities in the form of PE accelerate the process of PVC degradation due to the presence of free radicals formed during thermooxidative degradation of PE.…”
Section: Introductionmentioning
confidence: 98%
“…They are frequently used in wire, hose, tubing, moulding, extrusion, cable jacketing, and other industrial and automotive applications. 4 In several polymer composites, CPE is effective as a compatibilizer and adhesion promoter. 5 The demands of modern-day applications cannot be met solely by a single polymer.…”
Section: Introductionmentioning
confidence: 99%